Impact of the second-contact rule change on Setter performance, referee home advantage, and rally dynamics in NCAA volleyball - Forman, J. (Journal of Sports Sciences, 2025)
Purpose This study evaluates the impact of the NCAA`s 2024-25 rule change eliminating most ball-handling error (BHE) calls on second contacts directed to a teammate, testing its effects on overall BHE frequency, setter-specific risk, home-court asymmetry, and rally continuity.